The Islamic Mass Organization Contribution in Protecting the ReligiosityInclusive and Diversity in Indonesia - Masrukhin, M; Supaat, S (LPPM IAIN Kudus, 2018)
AbstractThis study aims to describe the contribution of Islamic community organizations (ormas) in maintaining diversity and religiousness are inclusive in Indonesia. This research uses qualitative approach and kind of research of Secondary Data Analysis (SDA). Data collection techniques with secondary data through the internet media. Data analysis techniques using three steps are: (1). Indentifying sources of information, (2). Gathering existing data, (3). Normalizing data of needed, (4). Analyzing data.The results of this study found: (1) The existence of Islamic organizations in Indonesia can be seen from three things: (a). Indonesia is a country that has diversity in the life of the community, the existence of Islamic organizations if managed properly communicative, controlled, transparent and accountable, it will be able to become a buffer in national development, (b) Popularity of Islamic organizations in the perspective of students there are five: Nahdlatul Ulama, Muhmmadiyah, Front Pembela Islam (FPI), Lembaga Dakwah Islam Indonesia and Hizbut Tahrir Indonesia. Organizations of Islamic societies that are considered popular by students are NU and Muhammadiyah, (c) The Government is obliged to discipline all existing organizations by making a set of rules in the form of Ormas Ordinances and Government Regulations. Real mass organizations are against the value of Pancasila and the UUD 1945, the government is entitled to be given warning, guidance until the revocation of the permit of the relevant organization, (2). Indonesia is a plural country. Pluralism can be seen from the diversity and religiousness of the community. The pluralism of the Indonesian people encourages us to unite in the unitary state of the unity of the Indonesian republic, (3). The formation of Islamic organizations aims to maintain unity and unity of the nation and also as a media aspirations of the community. The role of Islamic Organizations in maintaining diversity and religiousness that are inclusive in Indonesia can be seen two forms of Islamic mass organizations proven in history plays an important role in maintaining pluralism in Indonesia and Islamic organizations contribute positively to the development of Islamic education in Indonesia, (4). Islamic organizations in historical development have experienced many obstacles both internally and externally, government support is very important in the development of Islamic organizations in Indonesia.